Don’t Do What I Did!: An Early Middle Kingdom Block Statue with an Inscription Added Later for “the God’s Father…, the Royal Scribe and Prophet of Osiris, … Seniu (snw-jww)” - Fay, Biri (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
This small Middle Kingdom sculpture is approximately datable to the reign of King Amenemhat II and is one of the earliest preserved block statues. The inscription added hundreds of years after the statue’s creation, sometime between the Ramesside Period and the Third Intermediate Period reflects the regard in which the object was held, even in ancient times.